Reconstructing Indonesian Legislation on State Control of Mineral and Coal Resources to Promote Regional Welfare - Benito Asdhie Kodiyat MS; Ida Hanifah; Faisal (FASYA Press, 2025)
The recentralization of mineral and coal mining governance in Indonesia has generated constitutional debate regarding the implementation of the State's Right to Control under Article 33 paragraph (3) of the 1945 Constitution. Although the policy aims to strengthen national control over strategic natural resources, it has also reduced regional authority and raised concerns regarding accountability, regional welfare, and the constitutional balance between centralization and decentralization. This study aims to examine the constitutional framework of the State's Right to Control, analyze the legal implications of the shift from attributive to delegative regional authority, and formulate a balanced model for mining governance. This research employs a normative legal method using statutory and conceptual approaches. Primary, secondary, and relevant non-legal materials were analyzed through qualitative, descriptive, and prescriptive methods. The study concludes that the current centralized governance model weakens regional participation and supervisory functions, thereby creating constitutional and administrative inconsistencies. Accordingly, a balanced authority model is proposed to harmonize national strategic interests with regional autonomy and the constitutional objective of achieving the greatest prosperity of the people.